Kualitas Pendidikan di Daerah Pedesaan, Studi Kasus Desa Rowotamtu dan Tisnogambar (International Forum of Researchers and Lecturers, 2023)
Education is a process needed to obtain balance and perfection in the development of individuals and society. Education itself is faced with various problems that become obstacles to the quality of education itself. This can be seen in various aspects, some of which include the lack of adequate physical facilities such as the feasibility of buildings used in the learning process. These problems can hinder the development of students to reach their best potential and cause inequality in terms of access to quality education. There are differences in the quality of education in rural and urban areas, where rural areas have more specific challenges such as lack of school facilities, difficulty of access, and technological and social changes. In the context of education, technology has changed the way we learn, access information and communicate. Social changes, such as changing demographics, can also affect the way we design education systems. These factors create pressures on education that require creative thinking and innovative solutions. This research uses qualitative research methods through a phenomenological approach. The theoretical foundation used in this research is the functional structural theory proposed by Talcott Parson. Data collection in this study used interviews, observation, and documentation.